Common birds of IITA - Adeyanju, A.T.; Ottosson, U.; Shiiwua, M. (International Institute of Tropical Agriculture, 2012)
This IITA Guidebook will help you to identify many of the most common birds in the lake and forest areas of the campus. For each bird there is a photograph, a scientifi c name, common names in English and French, a description of the bird and notes on its ecology. The aim of this booklet is to encourage appreciation and enjoyment of Nigerian birds in their habitats.